Aging process, cognitive decline and Alzheimer`s disease: can strength training modulate these responses? - Matta Mello Portugal, Eduardo; Gomes Torres Vasconcelos, Poliane; Souza, Renata; Lattari, Eduardo; Sobral Monteiro-Junior, Renato; Machado, Sergio; Camaz Deslandes, Andrea (CNS & Neurological Disorders - Drug Targets, 2015)
Some evidence shows that aerobic training can attenuate the aging effects on the brain structures and functions. However, the strength exercise effects are poorly discussed. Thus, in the present study, the effects of strength training on the brain in elderly people and Alzheimer`s disease (AD) patients were revised. Furthermore, it a biological explanation relating to strength training effects on the brain is proposed. Brain atrophy can be related to neurotransmission dysfunction, like oxidative stress, that generates mitochondrial damage and reduced brain metabolism. Another mechanism is related to amyloid deposition and amyloid tangles, that can be related to reductions on insulin-like growth factor I concentrations. The brain-derived neurotrophic factor also presents reduction during aging process and AD. These neuronal dysfunctions are also related to cerebral blood flow decline that influence brain metabolism. All of these alterations contribute to cognitive impairment and AD. After a long period of strength training, the oxidative stress can be reduced, the brain-derived neurotrophic factor and insulin-like growth factor I serum concentrations enhance, and the cognitive performance improves. Considering these results, we can infer that strength training can be related to increased neurogenesis, neuroplasticity and, consequently, counteracts aging effects on the brain. The effect of strength training as an additional treatment of AD needs further investigation.
Keywords: elderly